Catalyst-Free Synthesis of Diastereomerically Pure 3-Sulfonylazetidin-2-ones via Microwave-Assisted Tandem Wolff Rearrangement–Staudinger Cycloaddition - Synofzik, Judith; Bakulina, Olga; Balabas, Olga; Dar’in, Dmitry; Krasavin, Mikhail (Synthesis, 2020)
A wide range of α-diazo-β-ketosulfones have been applied to thermally promoted tandem Wolff rearrangement – Staudinger [2+2] cycloaddition with imines to give polysubstituted β-lactam sulfones. Diastereomerically pure syn-diastereomers were obtained in good yields and the relative stereochemistry was confirmed by single-crystal X-ray crystallography. These findings significantly expand the scope of this transformation, in contrast to substantial limitations reported previously. Moreover, this methodology enables flexible exploration of new substitution patterns around the privileged β-lactam core for drug design and optimization.
Keywords: α-diazo-β-ketosulfones; Wolff rearrangement; Staudinger β-lactam synthesis; catalyst free; microwave irradiation